Upaya Meningkatkan Pola Berpikir Kritis Peserta Didik Melalui Probing Prompting Model’s Pada Mata Pelajaran Fiqih kelas VIII Di Madrasah Tsanawiyah Jam’iyah Mahmudiyah Tanjung Pura - Serliana, As’ad Badar, Khairuddin YM (LPPPI Publishing, 2023)
This study aims to determine the ability think critical students in learning Fiqh after the application of Probing Prompting Models in class VIII MTs Jam'iyah Mahmudiyah Tanjung Pura . This research is included in the class action research (Action Research). This research used a collaborative model, namely researchers and teachers in the field of Fiqh studies in class VIII MTs Jam'iyah Mahmudiyah Tanjung Pura . Subjects in Class VIII Action Research were class VIII students at MTs Jam'iyah Mahmudiyah Tanjung Pura with a total of 28 students. this researcher is the observation sheet and test which is in accordance with the research procedure by observing cycle I and cycle II. The application of the Probing Prompting Model's can be implemented well through two cycles. This can be seen through the activities that students in cycle I and cycle II have increased. The results of observing student activity in learning, which was originally in cycle I only achieved a score of 70% then increased by 17.5% to 87.5% in cycle II. There was a difference in students' critical thinking skills in class VIII MTs Jam'iyah Mahmudiyah Tanjung Pura between before and after carrying out classroom action research using the Probing Prompting Model's, it is known from the learning completeness in class VIII MTs Jam'iyah Mahmudiyah Tanjung Pura in the pre-cycle was 42.85% while in the first cycle it reached 67.85% and in the second cycle it was 82.14 %. After the Probing Prompting Model's students' critical thinking skills experienced an increase, this could be from the results of the pre-cycle critical thinking skills test which only achieved an average score of 67.85 (poor) and increased in cycle I to 73.92 (enough) and in cycle II increased again to 81.25 (good). The increase in critical thinking skills can also be seen in the increase in the percentage of student completeness, namely in the pre-cycle it was only 42.85% while in the first cycle it reached 67.85% and in the second cycle it was 82.14%.